Digital Marketing dan Pengaruhnya terhadap Peningkatan Penjualan Produk Rabbani Perspektif Ekonomi Islam - Setiana, Farida Arum; Kurniawan, Naufal (JIOSE: Journal of Indonesian Sharia Economics, 2024)
Rabbani products already have a market share with wide distribution in the community, especially in the Banjarnegara area. Not a few people choose Rabbani products as the mainstay Muslim clothing. One of the strategies carried out by Rabbani in increasing sales is to implement a digital marketing strategy. Based on these assumptions, this study was conducted to test and empirically prove the influence of digital marketing strategies on increasing sales turnover of Rabbani products in Banjarnegara. This research uses quantitative methods with the object of research of STAI Tanbihul Ghofilin Banjarnegara Students. In addition to questionnaires, research data was also obtained through interviews with store directors Rabbani Banjarnegara. The interview data was then analyzed to answer whether Rabbani's digital marketing strategy had met the requirements of Islamic law. The results of the study explained that digital marketing had an effect on increasing sales of Rabbani products by 37.4%. This research also resulted in the conclusion that the digital marketing strategy carried out by Toko Rabbani was in accordance with the principles of Islamic economics.